Tratamento de água de corpo lêntico com uso de coagulante orgânico e inorgânico - Lago Igapó II - Botelho, Jaqueline da Costa (2016)
The purpose of this study was to use organic coagulant Tanfloc SG and the inorganic coagulant aluminum sulfate coagulation through flocculation, sedimentation and processes, to treat the lake water Igapó II, it is located in the city of Londrina, to explore the potential use of for supply. For the experiment, the doses of the two coagulant chosen were varied C1 following concentrations: C1: 25mgL-1, C2: 45mgL-1 and C3: 65mgL-1: 65mgL-1.The treatment occurred using the jar test equipment with the same conditions of rapid mixing and flocculation used in the ETA of the Paraná Sanitation Company (Sanepar). The values of gradient mixture consisted of a time of rapid mixing, 450s-1 and four decays, 90s-1 52s-1 40s-1 and 30s-1. After the test, a study to compare the removal of turbidity and apparent color in addition to the pH change after 10, 20 and 30 minutes of settling, was done. The study sample was collected days before the tests. In the tests performed, both the Tanfloc SG, as for the aluminum sulfate concentration of 65mgL-1, showed good performance. It was found that the organic coagulant despite some variation in the pH parameter was not significant. It was observed that even larger flocs formed and are sedimented faster compared to those formed when inorganic coagulants. The results of the percent removal and statistical analysis indicated a large potential for Tanfloc SG when compared with sulfate of aluminum, in order that even without a filtration step was not carried out, some tests indicated that the values of the analyzed parameters they are within the maximums allowed by Order of potability 2914/11 the Ministry of Health and, therefore, could be used instead of aluminum sulfate, generally used in water treatment.